Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3324/haematol.2010.033167
|View full text |Cite
|
Sign up to set email alerts
|

Methylation profiling of mediastinal gray zone lymphoma reveals a distinctive signature with elements shared by classical Hodgkin's lymphoma and primary mediastinal large B-cell lymphoma

Abstract: The online version of this article has a supplementary Appendix. BackgroundMediastinal gray zone lymphoma is a newly recognized entity with transitional morphological and immunophenotypic features between the nodular sclerosis subtype of Hodgkin's lymphoma and primary mediastinal large B-cell lymphoma. Diagnostic criteria for mediastinal gray zone lymphoma are still challenging, and the optimal therapy is as yet undetermined. Epigenetic changes have been implicated in the loss of the B-cell program in classica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 42 publications
2
96
0
Order By: Relevance
“…The optimal therapeutic management of these lymphomas has not been determined. Recent biologic studies have begun to yield insights into the mechanisms modulating the plasticity of the neoplastic B cells and tumor microenvironment in CHL and DLBCL, 100,101 and they may provide data relevant to improved therapies. 102 …”
Section: Gray Zones Between Hodgkin Lymphoma and Primary Mediastinal mentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal therapeutic management of these lymphomas has not been determined. Recent biologic studies have begun to yield insights into the mechanisms modulating the plasticity of the neoplastic B cells and tumor microenvironment in CHL and DLBCL, 100,101 and they may provide data relevant to improved therapies. 102 …”
Section: Gray Zones Between Hodgkin Lymphoma and Primary Mediastinal mentioning
confidence: 99%
“…95,99 These observations suggested that a true biologic gray zone between these 2 entities could exist, a finding supported by profiling at the epigenetic level. 100 The 2008 WHO classification incorporates these new ideas and recognizes a provisional category of B-cell neoplasms with features intermediate between DLBCL and CHL. The category does not include the composite or sequential cases of both neoplasms.…”
Section: Gray Zones Between Hodgkin Lymphoma and Primary Mediastinal mentioning
confidence: 99%
“…61,62 Together with more recent genetic and epigenetic studies, they also support the inclusion in the WHO classification of the category large B-cell lymphoma, unclassifiable with features intermediate between DLBCL and HL. [63][64][65][66] …”
Section: Characterization Of Known Entities and Recognition Of New Camentioning
confidence: 99%
“…4 Analysis of methylation patterns has shown that mediastinal gray-zone lymphoma has a distinct epigenetic profile intermediate between CHL and PMBL but different from that of diffuse LBCL, suggesting that it is a distinct neoplasm, different from either CHL or PMBL. 20 The WHO classification in 2008 added a provisional category, B-cell lymphoma, intermediate between DLBCL and CHL. 21 It is defined as a B-lineage lymphoma that demonstrates overlapping clinical, morphological and/or immunophenotypic features between CHL and DLBCL, especially PMBL.…”
Section: Gray-zone Between Hl and Pmblmentioning
confidence: 99%